2014
DOI: 10.1097/mib.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Infliximab or Adalimumab on Vascular Endothelial Growth Factor and Angiopoietin 1 Angiogenic Factor Levels in Inflammatory Bowel Disease

Abstract: Circulating VEGF and Ang1 levels decrease after anti-TNF-alpha therapy and may predict response to treatment. Whether these changes are a direct effect of anti-TNF-alpha therapy or a sign of disease improvement remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…However, a different study found different results when comparing patients with or without strictures (85). Moreover, serum levels of YKL-40 are correlated with disease activity in UC patients, and patients with severe active disease have significantly higher levels than those with inactive UC (86).…”
Section: Growth Factorsmentioning
confidence: 95%
“…However, a different study found different results when comparing patients with or without strictures (85). Moreover, serum levels of YKL-40 are correlated with disease activity in UC patients, and patients with severe active disease have significantly higher levels than those with inactive UC (86).…”
Section: Growth Factorsmentioning
confidence: 95%
“…In fact, the level of VEGF has been used to predict the response to the treatment. 87,88 Clinically, patients with aggressive disease often have prominent pericolonic or perienteric vasculature on contrasted abdominal imaging, namely, the "comb sign." 89 In addition to the molecular studies, the association between splanchnic hemodynamic changes measured by Doppler ultrasound and disease activity of CD has been investigated.…”
Section: Blood Vesselsmentioning
confidence: 99%
“…The treatment target in IBD has shifted from symptom control alone towards symptom control in combination with mucosal repair, ideally achieved within 6‐12 months of commencing treatment. Nonetheless, this goal is not attained in the majority of patients . At present, mucosal healing can be achieved in not more than 40%‐50% of IBD patients .…”
Section: Discussionmentioning
confidence: 98%